The identification of FANCD2 DNA binding domains reveals nuclear localization sequences. Issue 14 (28th June 2017) - Niraj, Joshi; Caron, Marie-Christine; Drapeau, Karine; Bérubé, Stéphanie; Guitton-Sert, Laure; Coulombe, Yan; Couturier, Anthony M.; Masson, Jean-Yves
Abstract: Fanconi anemia (FA) is a recessive genetic disorder characterized by congenital abnormalities, progressive bone-marrow failure, and cancer susceptibility. The FA pathway consists of at least 21 FANC genes (FANCA-FANCV), and the encoded protein products interact in a common cellular pathway to gain resistance against DNA interstrand crosslinks. After DNA damage, FANCD2 is monoubiquitinated and accumulates on chromatin. FANCD2 plays a central role in the FA pathway, using yet unidentified DNA binding regions. By using synthetic peptide mapping and DNA binding screen by electromobility shift assays, we found that FANCD2 bears two major DNA binding domains predominantly consisting of evolutionary conserved lysine residues. Furthermore, one domain at the N-terminus of FANCD2 bears also nuclear localization sequences for the protein. Mutations in the bifunctional DNA binding/NLS domain lead to a reduction in FANCD2 monoubiquitination and increase in mitomycin C sensitivity. Such phenotypes are not fully rescued by fusion with an heterologous NLS, which enable separation of DNA binding and nuclear import functions within this domain that are necessary for FANCD2 functions. Collectively, our results enlighten the importance of DNA binding and NLS residues in FANCD2 to activate an efficient FA pathway.